Total chemical synthesis of sumoylated histone H4 reveals negative biochemical crosstalk with histone ubiquitylation. Issue 27 (20th March 2023) - Singh, Sumeet K.; Reyna, Andres; Xie, Xiaowen; Mao, Haibin; Ji, Meihuan; Zheng, Ning; Hsu, Peter L.; Chatterjee, Champak
Abstract : An efficient total chemical synthesis of site-specifically sumoylated histone H4 revealed its negative biochemical crosstalk with histone H2B ubiquitylation in vitro and in human cells. Abstract : An efficient total chemical synthesis of site-specifically sumoylated histone H4 was undertaken to generate homogenously modified mononucleosomes. These were tested as substrates in biochemical assays with the histone H2B-specific ubiquitin ligases Rad6 and Bre1, which revealed the strong inhibition of H2B ubiquitylation by SUMO. This novel negative biochemical crosstalk between SUMO and ubiquitin was also confirmed to exist in human cells.